Efektivitas Penggunaan Alat Peraga dengan Model Pembelajaran Inkuiri untuk Meningkatkan Keterampilan Generik Sains pada Materi Kinematika Gerak Kelas X SMA - Nur Khoiri; Rif'atul Fauziyah (Jurnal Penelitian Pembelajaran Fisika, 2020)
The purpose of this research is to find out the effectiveness of application motion kinematics props with the model of learning inquiry to the science generic skills of grade X students MIPA at SMA Negeri 15 Semarang. The design of the study using Posttest Only Control Design, in this design there were two randomly selected groups, where the first group was given a treatment called the experiment class, and the second group was not given a treatment called the control class. The population in this research is the grade X students of MIPA SMA Negeri 15 Semarang. The sample in the research was the grade X students of MIPA 1 as an experimental class amounting to 36 students and students of grade X MIPA 4 as a control class amounting to 36 students. The main instrument of research used is the observation sheet, that is by conducting observations performed by the observer when students perform practicum/experiments tailored to nine indicators of science generic skills. Analysis of the class observation sheet is obtained on average 84.51% with excellent criteria and control class 61.57% with good criteria. Statistical analysis shows the value of tcount 0,000 < ttable 0,05 with the equivalent of α = 0,05 significance, so that rejecting H0 and accepting Ha. There is a significant difference between the experimental class and control class, so the inquiry learning model assisted of kinematic props is effective against student’s Generic Science Skills.